Patient Preferences for Preventive Healthcare During the COVID-19 Pandemic in a Large Integrated Health System. (July 2022) - Stults, Cheryl D; Yan, Xiaowei; Deng, Sien; Dillon, Ellis C; Liang, Su-Ying; Jones, JB; Bhanushali, Minal; Frosch, Dominick L
The COVID-19 pandemic caused healthcare systems and patients to cancel or postpone healthcare services, particularly preventive care. Many patients still have not received these services raising concerns about the potential for preventable morbidity and mortality. At Sutter Health, a large integrated healthcare system in Northern California, we conducted a population-based email survey in August 2020 to evaluate perceptions and preferences about where, when, and how healthcare is delivered during the COVID-19 pandemic. In total, 3351 patients completed surveys, and 42.6% reported that they would "wait until they felt safe" before receiving a colonoscopy as compared to 22.4% for a mammogram. The doctor's office was the most common preferred location for receiving vaccines/shots (79.9%), though many also reported preferring an outdoor setting or in a car (63.7%). With over 40% of patients reporting that they would "wait until they feel safe" for a colonoscopy, healthcare systems could focus on promoting other evidence-based options such a fecal-occult blood test to ensure timely colon cancer screening.